2020
DOI: 10.1016/j.jiac.2019.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between lncRNA AC079767.4 variants and liver injury from antituberculosis treatment in West China

Abstract: Antituberculosis drug-induced adverse drug reactions (ADRs) has been attached the increasing attention currently. And many host genetic determinants of ADRs have been identified. However, the possible relationship between long non-coding RNA (lncRNA) and ADRs is little investigated in tuberculosis (TB). We conducted a prospective survey and comprehensively collected the information of diverse ADRs during antituberculosis therapy. Next, we analyzed whether single nucleotide polymorphisms (SNPs) within lncRNA AC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 20 publications
(24 reference statements)
0
5
0
Order By: Relevance
“… 23 Previous studies had confirmed that a variety of lncRNA gene variants were associated with the genetic risk of PTB, moreover, the expression of NEAT1 in PTB patients was abnormal. 14 , 15 To further analyze the role of NEAT1 gene variation in the pathogenesis of PTB, we explored the role of NEAT1 gene rs2239895, rs3741384, rs3825071, rs512715 variants in PTB. However, no significant result was found.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“… 23 Previous studies had confirmed that a variety of lncRNA gene variants were associated with the genetic risk of PTB, moreover, the expression of NEAT1 in PTB patients was abnormal. 14 , 15 To further analyze the role of NEAT1 gene variation in the pathogenesis of PTB, we explored the role of NEAT1 gene rs2239895, rs3741384, rs3825071, rs512715 variants in PTB. However, no significant result was found.…”
Section: Discussionmentioning
confidence: 99%
“… 12 , 13 In addition, the single nucleotide polymorphisms (SNP) in lncRNA genes have been shown to influence the susceptibility and clinical presentation of PTB. 14–16 The data of Zhao et al indicated that lncRNA AC079767.4 polymorphism had the potential to serve as a novel biomarker for PTB diagnosis. 14 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding treatment failure/recurrence, the lncRNA ( LINC01875 rs1055229) T allele, with a MAF of 24%, was associated with decreased treatment failure/recurrence, but a previous study associated this allele with increased tuberculosis drug-induced hepatotoxicity [45]. The NR1I2 rs7643645 G allele was associated with treatment failure/recurrence, but a previous report associated this with increased NAFLD severity [44].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier research studies have validated that multiple lncRNA genetic mutations were linked to the genetic susceptibility towards PTB [ 45 , 46 ]. A recent study found that the level of NEAT1 expression was anomalously high in the peripheral blood mononuclear cells of patients diagnosed with PTB [ 47 ].…”
Section: Roles Of Lncrnas In Tbmentioning
confidence: 99%